Surface materials and psychophysiology of vision - Gargiani, Roberto (EFPL Press, 2011)
Includes bibliographical references and index; The discovery of béton brut with malfacons : the worksite of the Unité d'Habitation at Marseille -- Acrobat training : the provocateur of new forms -- Unités d'Habitation at Rezé-Lès-Nantes, Berlin, and Briey-en-Forêt -- Chandigarh, or the cosmic vision -- Brutal skin in pisé, brick, and wood -- Machines à habiter for tropical visions and climates -- Automatisms and projections of sounds and images -- Toward a new stereotomy